Prof. Jun Hatazawa: boron neutron capture therapy (BNCT)—a star that needs the joint of multi-discipline knowledge - Fan, Wei-En (Therapeutic Radiology and Oncology, 2018)
Prof. Jun Hatazawa (Figure 1) is the Chairman of Department of Nuclear Medicine and Tracer Kinetics in Osaka University Graduate School of Medicine, Director of Department of Nuclear Medicine in Osaka University Hospital and Director of Osaka University positron emission tomography (PET) Molecular Imaging Center.